Ответы и объяснения

Лучший Ответ!
2013-03-27T15:47:20+00:00

(х-2)(х-3)=х(х+1)                                    (х+4)(х+6)-х^2=30

х^2-2х-3х+6=х^2+х                                х^2+4х+6х+24-х^2=30

6-5х=х                                                       10х+24=30

6х=6                                                          10х=6

х=1                                                             х=0,6

 

 

(х-5)(х+1)-х=х^2+5

х^2-5х+х-5=х^2+5

-4х-5=5

4х=-10

х=-0,25

 

 

(х-1)(х-3)=(х-2)(х-4)

х^2-х-3х+3=х^2-2х-4х+8

3-4х=8-6х

2х=5

х=о,25